Konseptualisasi Model Pendidikan Islam Integratif di Madrasah Ibtidaiyah (MI) Indonesia - Ahmad Yusuf (DAYAH: Journal of Islamic Education, 2021)
Islamic education always places the Qur'an and the Sunnah as its source, method, and goal. Efforts to define the meaning of education become the main issue and become the basis for implementing Islamic education. This article aims to uncover and describe and at the same time reconstruct the model of Islamic education, especially in Madrasah Ibtidaiyyah (MI). Using a descriptive analysis approach from relevant literature sources will provide a complete description of the Islamic model in Madrasah Ibtidaiyyah. In this study, it can be argued that Islamic education has unique characteristics compared to the concept of education in general. Besides having a transcendental aspect, it is also very considerate of kawniyyah aspects (ṭabī’ah al-insān and ṭabī’ah al-ḥayāh). Based on the findings of this article, it can give implications for the model of Islamic Education in Madrasah Ibtidaiyah, which should not only develop religious material but also pay attention to available material, both of which must be integrated so that there is no dichotomy of knowledge that creates inequality for the output of Madrasah Ibtidaiyyah itself in the era of globalization.